STRATEGI PENGEMBANGAN GEOPRODUK LAUT DALAM UPAYA PERTUMBUHAN EKONOMI LOKAL DESA JEPITU, GIRISUBO-GUNUNGKIDUL - Mulyaningsih, Sri -; Mulyaningsih, Sri Mulyaningsih; Rahmawati, Nur; Vienastra, Septian; Suhartono, Suhartono; Wahyu Jati, Michael Fatah Wahyu Jati; Istiqomah, Nurul Istiqomah; Emiliana, Maria Emiliana; Hidayati, Fika Hidayati; Wardana, M. Arif Wardana (Universitas Trisakti, 2025)
Socio-political uncertainty, sluggish economic growth, and the looming threat of a potential